1998
DOI: 10.1038/sj.bmt.1701443
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adaptation of patients and families following bone marrow transplantation: a prospective, longitudinal study

Abstract: Summary:Using a prospective, repeated measures design, this study investigated the psychosocial functioning of patients and a close relative pre-and post-allogeneic and autologous bone marrow transplantation (BMT). All patients (n = 28) undergoing BMT in a 1 year period, and their relatives, were interviewed 1 week pre-transplant and at 3, 6 and 12 months post-BMT, using quantitative and qualitative measures. Pre-transplant data revealed a high level of anxiety (61% with moderate to severe anxiety), and a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 17 publications
1
57
2
2
Order By: Relevance
“…Among patients with other types of malignancies, the proportion that exceeded cutoff scores on screening measures of emotional distress varied across studies. For the most part, the levels of distress in the current sample are a bit higher than those reported in investigations that used the same instrument (HADS) to assess patients prior to autologous transplantation, 27,29 or in samples that were mixed for type of transplant [30][31][32] (see Table 5). Among the few exceptions, depressive symptoms were more common (30%) in the Wettergren et al 29 study and cases of anxiety were more prevalent (61%) in the Keogh et al 31 study.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Among patients with other types of malignancies, the proportion that exceeded cutoff scores on screening measures of emotional distress varied across studies. For the most part, the levels of distress in the current sample are a bit higher than those reported in investigations that used the same instrument (HADS) to assess patients prior to autologous transplantation, 27,29 or in samples that were mixed for type of transplant [30][31][32] (see Table 5). Among the few exceptions, depressive symptoms were more common (30%) in the Wettergren et al 29 study and cases of anxiety were more prevalent (61%) in the Keogh et al 31 study.…”
Section: Discussionmentioning
confidence: 69%
“…For the most part, the levels of distress in the current sample are a bit higher than those reported in investigations that used the same instrument (HADS) to assess patients prior to autologous transplantation, 27,29 or in samples that were mixed for type of transplant [30][31][32] (see Table 5). Among the few exceptions, depressive symptoms were more common (30%) in the Wettergren et al 29 study and cases of anxiety were more prevalent (61%) in the Keogh et al 31 study. The results concerning physical functioning are not directly comparable, because different measures were used in previous investigations and the percentage of patients considered at risk for functional impairment was not reported.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The overall level of distress of caregivers equaled that of the recipients, whereas caregivers experienced even greater difficulty with family relationships. A longitudinal study of 28 BMT recipients and a 'close relative,' 19 which included pre-transplant to 12 months post transplant, found that 88% of the caregivers were highly distressed pre-transplant as well as post transplant; this exceeded the number of BMT recipients who were equally distressed. Zabora et al 20 also examined an adaptation of both the recipient and the caregiver using structured interviews and standardized measures over a period of 24 months.…”
Section: Introductionmentioning
confidence: 99%